Reavaliando a gratidão: implicações para a ética das virtudes contemporânea - Carvalho, Talyta Cristina de (2024)
The thesis explores gratitude from the perspective of contemporary virtue ethics, a field systematically established since the seminal article "Modern Moral Philosophy" by Gertrude Elizabeth Anscombe in 1958. The main objective is to defend gratitude as a virtue, emphasizing the relevance of this approach to moral philosophy. The research examines the theoretical foundations of fundamental concepts, such as virtue and phronesis, based on Aristotle's work and its application to the development of contemporary virtue ethics. In this field, the main theoretical references used to articulate this objective include Anscombe herself, as well as the works of Alasdair MacIntyre and Philippa Foot. Our hypothesis suggests that approaching gratitude from this perspective is fruitful for moral philosophical understanding. In conclusion, we propose that this study, besides contributing original reflections to the field, also serves as an incentive for new studies on contemporary virtue ethics in the Brazilian academic community